Assessment of electricity supply adequacy for tsunami refuge shelter planning in Universitas Andalas - Budikusuma Arif; Adrianti Adrianti; Nasir Muhammad; Nofendra Riko; Hakimah Ab Aziz Nur (E3S Web of Conferences)
Padang City is an earthquake-tsunami-prone area; therefore, preparedness to anticipate disasters is essential. The city has made evacuation routes and provided Temporary Evacuation Shelters and Final Evacuation Shelters. Universitas Andalas (Unand) is in the safe zone of a tsunami disaster and can be used as a final evacuation shelter. When a disaster occurs, most of the electrical network experiences damage. Hence, only local electrical power supply can be relied on. Unand has gensets and PV that can supply the refugee shelters. This study aims to analyse Unand’s power supply ability to provide electricity for planned refugee shelters. The research started with shelter location selection, measuring shelter area, determining shelter capacity, calculating shelter electric demand, and analysing the local supply adequacy in serving the electric demand. The results show that the shelters can accommodate 3704 refugees, and the peak demand is 55.1 Kw in the evenings. The peak demand is far lower than the power supply’s maximum output. Then, based on the demand and generating output, power flow simulations are carried out to determine the electrical conditions in the network. It is found that Unand can meet the refugee’s electrical power needs and the electricity quality is within standard.